Human Resource Management: A Bibliometric Review of Conceptual Foundations and Research Growth - Loso Judijanto; Gopur Gopur (Westscience Press, 2026)
This study aims to map the conceptual foundations and research growth of Human Resource Management (HRM) through a comprehensive bibliometric analysis. Data were collected from the Scopus database using relevant keywords related to HRM and its associated domains. The dataset was analyzed using VOSviewer to examine publication trends, keyword co-occurrence, co-authorship networks, and thematic evolution. The findings reveal that HRM research has developed into a highly interdisciplinary field, integrating perspectives from organizational behavior, psychology, healthcare, and information systems. Core themes such as decision making, organizational management, and employee-related outcomes remain dominant, while emerging topics including digital HRM, machine learning, and sustainable development indicate a shift toward technology-driven and sustainability-oriented research. Additionally, the results highlight strong global collaboration patterns and an increasing emphasis on systematic reviews, reflecting the growing maturity of the field. This study contributes to the literature by providing a structured overview of HRM research and identifying future directions, particularly in the areas of digital transformation, sustainability integration, and cross-sector applications